Digital village construction, human capital and the development of the rural older adult care service industry - Liu, Shengyou; Zhu, Shaopeng; Hou, Zhiping; Li, Changgui (Frontiers in Public Health, 2023)
Background The advancement of digital villages in China is shaped by the degree of human capital within the rural labor force, which not only restricts the potential of digital village but also influences the impact of digital empowerment on the progression of the rural older adult care service industry. Materials and methods Using panel data from 30 Chinese provinces between 2011 and 2020, we created benchmark and threshold regression models to investigate the influence of digital village construction on the development of the rural older adult care service industry and to delineate the threshold effects of human capital on it. We further scrutinized the correlation between the two systems, along with the factors that affect it, through a coupling coordination model. Results Preliminary, the baseline regression outcomes show that the digital village construction is conducive to the progression of the rural older adult care service industry (p < 0.05). Moreover, we identified a significant nonlinear threshold relationship between the digital village, human capital, and the advancement of the rural older adult care service industry (HUM1ST, p < 0.05; HUM2DT, p < 0.01; HUM3DT, p < 0.01). These results indicate that the digital technology’s effect on the development of the rural older adult care service industry is limited by the rural human capital level. Lastly, we found that higher levels of human capital enhance the coupling of the digital village with the rural older adult care service industry (p < 0.01), with the influence of per capita education level being the most pronounced (CoefHUM1 > CoefHUM2 > CoefHUM3). Conclusion The digital village substantially empowers the rural older adult care service industry, with human capital exhibiting a significant threshold effect on this empowerment. Furthermore, variances in the level of human capital have a considerable impact on the integration of the digital village and the rural older adult care service industry.